From Playboys to Disco Pigs: Irish Identities on a World Stage - Gunn, Linda (ABEI Journal, 2009)
This article examines the subject of Irish identity in contemporary Irish theatre productions, focusing a selection of plays showcased to a worldaudience through receiving their UK premieres at the Traverse TheatreEdinburgh during Edinburgh Fringe Festivals over the last ten years. It considers several issues around the theme of whether Irish identity is a concern in contemporary Irish theatre and, if so, why and in what ways has it been used. This is carried out by examining productions which address Irish identity directly, productions which address it indirectly and some which, apparently, do not appear to be concerned with it at all, using the latter category to discuss the question of influenced readings and interpretations.